Gdzie rozgrywa się akcja Dzieci szatana Stanisława Przybyszewskiego? Destrukcja i rekonstrukcja świata przedstawionego - Wedemann, Marek (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
One of the characteristics that make Stanisław Przybyszewski’s novels stand out from other contemporary works is the deliberately limited description of the outside world up to the point of blurring the identity of the location where the plot of a given work takes place. In the case of Dzieci Szatana (Satan’s Children), (German Satans Kinder, 1897; Polish edition 1899), one may even talk about ‘a total destruction of the represented world’ (Gabriela Matuszek). At the same time, the author’s numerous comments apparently allow for translating this ‘destruction’ happening in the course of the creative process into a ‘reconstruction’ that corresponds to it in the process of reading. It is through reviewing in more detail and combining various pieces of information included in Dzieci Szatana that directly or indirectly refer to the place of action, as well as confronting them with the biographical, historical and geographic contexts that one may identify with surprising precision the exact place represented in the text and, as a result, to uncover an entirely new aspect of novel axiology.